Development and validation of the Health Promoting Behaviour for Bloating (HPB-Bloat) scale - Abdullah, Nurzulaikha; Kueh, Yee Cheng; Kuan, Garry; Wong, Mung Seong; Yahaya, Fatan Hamamah; Abd Samat, Nor Aslina; Zulkifli, Khairil Khuzaini; Lee, Yeong Yeh (PeerJ, 2021)
Background Health management strategies may help patients with abdominal bloating (AB), but there are currently no tools that measure behaviour and awareness. This study aimed to validate and verify the dimensionality of the newly-developed Health Promoting Behaviour for Bloating (HPB-Bloat) scale. Methods Based on previous literature, expert input, and in-depth interviews, we generated new items for the HPB-Bloat. Its content validity was assessed by experts and pre-tested across 30 individuals with AB. Construct validity and dimensionality were first determined using exploratory factor analysis (EFA) and Promax rotation analysis, and then using confirmatory factor analysis (CFA). Results During the development stage, 35 items were generated for the HPB-Bloat, and were maintained following content validity assessment and pre-testing. One hundred and fifty-two participants (mean age of 31.27 years, 68.3% female) and 323 participants (mean age of 27.69 years, 59.4% male) completed the scale for EFA and CFA, respectively. Using EFA, we identified 20 items that we divided into five factors: diet (five items), health awareness (four items), physical activity (three items), stress management (four items), and treatment (four items). The total variance explained by the EFA model was 56.7%. The Cronbach alpha values of the five factors ranged between 0.52 and 0.81. In the CFA model, one problematic latent variable (treatment) was identified and three items were removed. In the final measurement model, four factors and 17 items fit the data well based on several fit indices (root mean square error of approximation (RMSEA) = 0.044 and standardized root mean squared residual (SRMR) = 0.052). The composite reliability of all factors in the final measurement model was above 0.60, indicating acceptable construct reliability. Conclusion The newly developed HPB-Bloat scale is valid and reliable when assessing the awareness of health-promoting behaviours across patients with AB. Further validation is needed across different languages and populations.
Keywords: Abdominal bloating; Questionnaire; Health promoting behavior; Self-management; Lifestyle; Quality of life